Exploring The Influence of Information Overload on Purchasing Avoidance With Consumer Confusion as a Mediator - Larisa Pradisti; Mohamad Rifqy Roosdhani; Nurul Komaryatin (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2026)
In the digital age, information overload occurs when individuals are overwhelmed by excessive and conflicting data, complicating decision-making. This overload leads to consumer confusion, making it hard to process available options and often resulting in purchasing avoidance. Studies show that consumer confusion mediates the relationship between information overload and purchasing avoidance, heightening anxiety and delaying decisions. While more information can sometimes help, it frequently causes confusion and fatigue, which ultimately hinders purchasing decisions. Our study used quantitative sampling with a purpose to collect and analyze data from 156 students of Jenderal Soedirman University, Purwokerto. After that, we used Structural Equation Modeling PLS data collected through questionnaires to test the model. Our findings show how effective consumer confusion can increase information overload and purchasing avoidance. Furthermore, business owners should focus on reducing consumer confusion to reduce the negative impact of information overload on purchasing decisions.